Efektivitas Anticestoda Ekstrak Daun Miana (Coleus blumei Bent) terhadap Cacing Hymenolepis microstoma pada Mencit - Y Ridwan; F Satrija; L K Darusman; F Handharyani (Faculty of Animal Science, Bogor Agricultural University, 2010)
Coleus blumei is a herbal plant used in the traditional medicine in Indonesia to expel the intestinal worm infections. Previous in vitro study showed that ethanol extract had the strongest anticestode activity compared to chloroform, hexane and aquaous extracts. The aim of the study was to evaluate the effectivity of anticestode of ethanol leaves extract againts Hymenolepis microstoma infections in mice. The plant extract was tested against H. microstoma infections in the single doses of 250, 500, 1000, and 2000 mg kg-1 body weight. Dose were administered to H. microstoma infected mice for 3 consecutive days. The efficacy of the leave extract was determined in terms of eggs per gram of feces (EPG) and worms reduction at necropsy. The results showed that the efficacy of leaves extract was dose dependent. The maximum efficacy of leave extract was observed with 2000 mg/kg dose reducing the EPG and worm counts by 55.46%-69.75% and 63.83% respectively. The standard anticestodal drug, praziquantel at 25 mg/kg single dose revealed 100% reduction in both of EPG and worm counts. The study suggests that the leaves extract of C. blumei possesses significant anticestodal efficacy and supports its use in traditional medicine. Key words: anticestode, Coleus blumei extract, Hymenolepis microstoma